Anti-Inflammatory Effects of Interleukin-19 in Vascular Disease - Ross N. England; Michael V. Autieri (Hindawi Limited, 2012)
Despite aggressive dietary modification, lipid-lowering medications, and other interventional medical therapy, vascular disease continues to be a leading cause of mortality in the western world. It is a significant medical and socioeconomic problem contributing to mortality of multiple diseases including myocardial infarction, stroke, renal failure, and peripheral vascular disease. Morbidity and mortality of vascular disease are expected to worsen with the increasing number of patients with comorbid conditions such as obesity, metabolic syndrome, and diabetes mellitus type 2. Vascular diseases such as atherosclerosis, restenosis, and allograft vasculopathy are recognized to be driven by inflammation, and as such, cytokines which mediate inflammation not only represent important targets of rational therapy, but also can be considered as possible therapeutic modalities themselves. In this paper, we will examine the role of inflammatory cytokines and lymphocyte Th1/Th2 polarity in vascular inflammation, with a focus on atherosclerotic vascular disease. We will then introduce a recently described Th2 interleukin, interleukin-19 (IL-19), as a previously unrecognized mediator of vascular inflammatory disorders. We will review our current understanding of this interleukin in health and disease and present the possibility that IL-19 could represent a potential therapeutic to combat vascular inflammatory disease.